PELATIHAN PERENCANAAN DAN PENGELOLAAN KEUANGAN BAGI KUBE SARI JAYA DI DESA SUMERTA KAUH-DENPASAR - Ni Putu Ayu Kusumawati; Ni Made Wisni Arie Pramuki; Ni Putu Trisna Windika Pratiwi; Putu Cita Ayu; Putu Nuniek Hutnaleontina; Ni Putu Yeni Yuliantari; Gusti Alit Suputra (JURNAL SEWAKA BHAKTI, 2023)
KUBE Sari Jaya is a small business consisting of five members, whose production focus is the manufacture of traditional cakes. The partner's knowledge of financial management is still low, so business money is often combined with personal money. This will certainly have an impact on the unhealthy cash flow in the business. In addition, intense competition with similar businesses requires that Kube members must innovate in the packaging of their traditional snacks so that they have an attractive appearance and the resulting traditional snacks can be widely known by the wider community. The purpose of this service activity is to provide knowledge to partners, how important financial management is for business sustainability, besides that labeling in the form of stickers on traditional snack packages will directly make the appearance of snacks more attractive. The method used is in the form of lectures and discussions as well as providing training to partners on good financial management. The results of this service activity are being able to increase partners' knowledge related to financial management which includes how to record business transactions, how to calculate HPP, how to calculate the level of business profits and provide education to partners with labeling which will make it easier for people to get to know the products we offer for. This service activity is expected to have a positive impact on the sustainability of Kube Sari Jaya.